Analisis Pengaruh Non Performing Loan (NPL) dan Loan to Deposit Ratio (LDR) terhadap Return On Asset (ROA) pada Bank Umum Milik Negara - Pakaya, Srie Isnawati; Ishak, Idham Masri; Paramani, Regita Nur Rizka (Economic Reviews Journal, 2024)
This research aimed to ascertain to what extent the Non Performing Loan (NPL) and Loan to Deposit Ratio (LDR) affected Return on Assets (ROA) in state- owned commercial banks listed on the Indonesia Stock Exchange from 2013 to 2022. The data collection techniques included documentation and a literature review. It employed a purposive sampling in which the research population comprised state- owned commercial banks listed on the Indonesia Stock Exchange from 2013 to 2022, with a sample size of four companies. Furthermore, the data analysis was done through classical assumption tests, hypothesis testing, and multiple regression analysis. The findings indicated that: 1) Partially, Non-Performing Loan did not have a significant effect on Return on Assets. 2) Partially, Loan to Deposit Ratio had a significant effect on Return on Assets. 3) Simultaneously, the variables Non- Performing Loan and Loan to Deposit Ratio had a significant effect on Return on Assets.